2020
DOI: 10.1038/s41598-020-61929-9
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of graphene nanocomposites from aqueous silver nitrate using graphene oxide’s peroxidase-like and carbocatalytic properties

Abstract: the present study evaluates the role of graphene oxide's (Go's) peroxidase-like and inherent/ carbocatalytic properties in oxidising silver nitrate (AgNO 3 ) to create graphene nanocomposites with silver nanoparticles (GO/Ag nanocomposite). Activation of peroxidase-like catalytic function of Go required hydrogen peroxide (H 2 o 2 ) and ammonia (nH 3 ) in pH 4.0 disodium hydrogen phosphate (na 2 Hpo 4 ). Carbocatalytic abilities of GO were triggered in pH 4.0 deionised distilled water (ddH 2 O). Transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Certainly, pH is what matters here since the typical surface plasmon resonance peak emerge at higher pH [34]. Indeed, it was reported that silver clusters/nanoparticles synthesized on GO surface do not necessarily exhibit the distinguishable absorbance peak, instead AgNP is displayed as the higher "background" of the absorbance spectrum [50]. Lower diameter of spherical nanoparticles also decreases the absorption cross-section [51] and, last but not least, net amount of AgNPs in the bulk GO_Ag nanomaterial is quite low.…”
Section: Spectroscopic and Microscopic Characterizationmentioning
confidence: 99%
“…Certainly, pH is what matters here since the typical surface plasmon resonance peak emerge at higher pH [34]. Indeed, it was reported that silver clusters/nanoparticles synthesized on GO surface do not necessarily exhibit the distinguishable absorbance peak, instead AgNP is displayed as the higher "background" of the absorbance spectrum [50]. Lower diameter of spherical nanoparticles also decreases the absorption cross-section [51] and, last but not least, net amount of AgNPs in the bulk GO_Ag nanomaterial is quite low.…”
Section: Spectroscopic and Microscopic Characterizationmentioning
confidence: 99%
“…The high reinforcing properties of graphene are due to the two-dimensional structure with high specific surface area of 2630 m 2 g −1 26 . Graphene, having good biological properties, has been extensively studied in biological applications, including drug delivery 27 , biosensing 28 , tissue engineering 29 , and bioimaging 30 .…”
mentioning
confidence: 99%
“…GO is a single-atom layered material composed of carbon, hydrogen and oxygen molecules through the oxidation of inexpensive and abundant graphite crystals [ 30 , 44 , 45 ]. Furthermore, GO has good biological properties and has been widely used in biomedical field, including drug delivery [ 46 ], cancer therapy [ 47 , 48 ], biosensing [ 49 ], tissue engineering [ 50 ], and bioimaging [ 51 ]. The use of GO can enhance cell proliferation and differentiation characteristics.…”
Section: Discussionmentioning
confidence: 99%